Percolation scaling in composites of exfoliated MoS 2 filled with nanotubes and graphene - COLEMAN, JONATHAN; DUESBERG, GEORG; MCEVOY, NIALL (My University, 2012)
Applications of films of exfoliated layered compounds in many areas will be limited by their relatively low electrical conductivity. To address this, we have prepared and characterised composites of a nano-conductor (nanotubes or graphene) embedded in a matrix of exfoliated MoS 2 nanosheets. Solvent exfoliation of MoS 2 nanosheets, followed by blending with dispersions of graphene or nanotubes allowed the formation of such composite films by vacuum filtration. This gave spatially uniform mixtures with fully tuneable nano-conductor content. By addition of the nano-conducting phase, it was possible to vary the electrical conductivity of the composite over nine orders of magnitude. For both filler types the conductivity followed percolation scaling laws both above and below the percolation threshold. In the case of SWNT-filled composites, conductivities as high as ~40 S m -1 were achieved at volume fractions as low as ~4%
PUBLISHED
Keywords: films; films; Nanoscience & Materials